Synergistic effects of straw and biochar co-application on soil biological restoration and pepper yield enhancement in red soils from China - Cheng, Chen; Ren, Zhaoyan; Wang, Wenqian; Li, Xing; Liao, Yawen; Luo, Han; Yang, Yang; Zhu, Bo; Gao, Zhiqiang; Yao, Fengxian (Frontiers in Agronomy, 2025)
AimsContinuous cropping of peppers not only degrades soil quality but also impairs the normal growth and development of peppers grown in greenhouse production systems in the red soil region of south China. It remains unclear whether the negative effects can be alleviated by applying straw and its carbonization.MethodsIn 2021-2022, a pot experiment was conducted with four treatments: a control group with no organic material added (CK), the addition of biochar (B), straw (S), and a combination of biochar and straw (BS) added to the soil. The changing characteristics of pepper growth and yield, soil quality and rhizosphere soil microbial community were determined.ResultsResults indicated that the application of S and B were beneficial to the formation of high yield of pepper and improved the physicochemical properties, enzyme activities, microbial quantity of continuous cropping soil. Among them, the yield of BS was significantly increased by 144.37% on average. More importantly, BS treatment also demonstrated superior rhizosphere soil microbiome enhancement, with microbial populations increasing by 425.42% (bacteria), 946.68% (fungi), and 232.95% (actinomycetes) compared to control. Bacterial diversity indices showed significant improvement (Chao1 + 92.77%, Shannon +39.37%), accompanied by targeted microbial community restructuring that enriched beneficial Bacteroidota and Verrucomicrobiota while suppressing Proteobacteria and pathogenic Ascomycota. These microbiome modifications correlated strongly with enhanced soil enzyme activities and improved physicochemical properties.ConclusionsThe straw-biochar co-application increased pepper yields by 144.37% by improving soil fertility and microbial diversity through rhizosphere microbiome modulation (reducing pathogens and enhancing nutrient cycling). This integrated approach provides a sustainable strategy for intensive continuous cropping systems.